Analysis of Speech Acts Components Found in the "Mata Najwa" Talk Show - Amanda, Loly Grenia; Jufrizal, Jufrizal (English Language and Literature, 2024)
This research aims to examine the speech act components and types of speech acts in the "Mata Najwa" talk show program. The focus of this research is the utterances of Najwa Shihab and three Indonesian presidential candidates in 2024. This research uses a descriptive-qualitative method. The theories used in this research are the theory of speech acts by Austin (1962) to determine the components of speech acts and the theory of speech acts by Searle (1969) to determine the types of speech acts. The results of the analysis in this research, in the form of action from the three components of speech acts, show that the most common form of locutionary act is opinion, the most common form of illocutionary act is conveying view, and the most common form of perlocutionary act is 'understanding from the listener'. Meanwhile, the type of speech act that is most dominant is representative.